Keunggulan Bersaing Berkelanjutan Berbasis Inovasi dan Kearifan Lokal Pada Usaha Kecil dan Menengah Makanan Tradisional di Pekanbaru - Rosmayani Rosmayani; Annisa Mardatillah (Universitas Riau, 2021)
Business actors' competition in capturing market share has made it essential for business actors to implement sustainable competitive advantage through local wisdom and innovation. It is expected to improve product quality sustainably. This study aims to analyze sustainable competitive advantage based on local wisdom and innovation in small and medium enterprises of Riau Malay traditional food in Pekanbaru. The research method used is qualitative with observation, interview, and literary techniques. The sampling technique used was purposive sampling on ten business actors and triangulation as the analysis technique in this study. This study's findings are that local wisdom factors and product innovation are a source of sustainable competitive advantage in the micro and small business sector of Riau Malay traditional food in Pekanbaru. Although innovations made in traditional Riau Malay food products, this has not made the product more homogeneous but still thick with its uniqueness and authenticity. The resources owned's heterogeneity is reflected in local knowledge, local skills, local resources, and local values in traditional Riau Malay food products, a differentiator that competitors cannot imitate.